Controlling and quantifying protein concentration in Escherichia coli. (22nd May 2019) - Speer, Shannon L.; Guseman, Alex J.; Patteson, Jon B.; Ehrmann, Brandie M.; Pielak, Gary J.
Abstract: The cellular environment is dynamic and complex, involving thousands of different macromolecules with total concentrations of hundreds of grams per liter. However, most biochemistry is conducted in dilute buffer where the concentration of macromolecules is less than 10 g/L. High concentrations of macromolecules affect protein stability, function, and protein complex formation, but to understand these phenomena fully we need to know the concentration of the test protein in cells. Here, we quantify the concentration of an overexpressed recombinant protein, a variant of the B1 domain of protein G, in Tuner (DE3)™ Escherichia coli cells as a function of inducer concentration. We find that the protein expression level is controllable, and expression saturates at over 2 m M upon induction with 0.4 m M isopropyl β‐d ‐thiogalactoside. We discuss the results in terms of what can and cannot be learned from in‐cell protein NMR studies in E. coli .